Brain Development Measured by MRI - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
MRI data read as normal on 88 male and female patients aged 3 months to 30 years and on 73 healthy male volunteers aged 21 to 70 years were quantified and the volumes of cortical white matter, gray matter, and CSF were computed in a study at the Department of Veterans Affairs Medical Center, and the Department of Psychiatry and Behavioral Science, Stanford University School of Medicine, CA.